Linking biofilm growth to fouling and aeration performance of fine-pore diffuser in activated sludge. (1st March 2016) - Garrido-Baserba, Manel; Asvapathanagul, Pitiporn; McCarthy, Graham W.; Gocke, Thomas E.; Olson, Betty H.; Park, Hee-Deung; Al-Omari, Ahmed; Murthy, Sudhir; Bott, Charles B.; Wett, Bernhard; Smeraldi, Joshua D.; Shaw, Andrew R.; et al.
Abstract: Aeration is commonly identified as the largest contributor to process energy needs in the treatment of wastewater and therefore garners significant focus in reducing energy use. Fine-pore diffusers are the most common aeration system in municipal wastewater treatment. These diffusers are subject to fouling and scaling, resulting in loss in transfer efficiency as biofilms form and change material properties producing larger bubbles, hindering mass transfer and contributing to increased plant energy costs. This research establishes a direct correlation and apparent mechanistic link between biofilm DNA concentration and reduced aeration efficiency caused by biofilm fouling. Although the connection between biofilm growth and fouling has been implicit in discussions of diffuser fouling for many years, this research provides measured quantitative connection between the extent of biofouling and reduced diffuser efficiency. This was clearly established by studying systematically the deterioration of aeration diffusers efficiency during a 1.5 year period, concurrently with the microbiological study of the biofilm fouling in order to understand the major factors contributing to diffuser fouling. The six different diffuser technologies analyzed in this paper included four different materials which were ethylene-propylene-diene monomer (EPDM), polyurethane, silicone and ceramic. While all diffusers foul eventually, some novel materials exhibited fouling resistance. The material type played a major role in determining the biofilm characteristics (i.e., growth rate, composition, and microbial density) which directly affected the rate and intensity at what the diffusers were fouled, whereas diffuser geometry exerted little influence. Overall, a high correlation between the increase in biofilm DNA and the decrease in αF was evident (CV < 14.0 ± 2.0%). By linking bacterial growth with aeration efficiency, the research was able to show quantitatively the causal connection between bacterial fouling and energy wastage during aeration. Graphical abstract: Highlights: The link between aeration efficiency decrease and fouling have been established. This research provides directly measured evidence of the connection between biofouling and reduced diffuser efficiency. The aeration efficiency of six different aeration diffusers during a 1.5 year period was systematically studied. Molecular tools were applied in order to understand the major factors contributing to diffuser fouling.